Improved Visual Cognition through Stroboscopic Training - Appelbaum, Lawrence Gregory; Schroeder, Julia E.; Cain, Matthew S.; Mitroff, Stephen R. (Frontiers in Psychology, 2011)
Humans have a remarkable capacity to learn and adapt, but surprisingly little research has demonstrated generalized learning in which new skills and strategies can be used flexibly across a range of tasks and contexts. In the present work we examined whether generalized learning could result from visual–motor training under stroboscopic visual conditions. Individuals were assigned to either an experimental condition that trained with stroboscopic eyewear or to a control condition that underwent identical training with non-stroboscopic eyewear. The training consisted of multiple sessions of athletic activities during which participants performed simple drills such as throwing and catching. To determine if training led to generalized benefits, we used computerized measures to assess perceptual and cognitive abilities on a variety of tasks before and after training. Computer-based assessments included measures of visual sensitivity (central and peripheral motion coherence thresholds), transient spatial attention (a useful field of view – dual task paradigm), and sustained attention (multiple-object tracking). Results revealed that stroboscopic training led to significantly greater re-test improvement in central visual field motion sensitivity and transient attention abilities. No training benefits were observed for peripheral motion sensitivity or peripheral transient attention abilities, nor were benefits seen for sustained attention during multiple-object tracking. These findings suggest that stroboscopic training can effectively improve some, but not all aspects of visual perception and attention.